Large solar assisted grounds source heat pump systems - Design based on a new low-temperature solar collector model - Malmberg, Alexander (My University, 2018)
In order to reduce the climate impact, it is important to reduce the energy consumption in all sectors. A heat pump could be used to fulfill the heating and the cooling demand of a building. The disadvantage of a ground source heat pump is the relatively high investment cost. A major part of the total investment cost for such a energy system is because of the borehole thermal energy storage. When the heating and the cooling demand is not of the same size, the borehole thermal energy storage will be dimensioned so that the temperature in the storage won't drop too much after a few years. If the temperature in the storage drops it will lead to a performance drop in the heat pump. This master's thesis examines the possibility of reducing the size of the borehole thermal energy storage by recharging the storage with a low-temperature solar collector. The cost saving for the borehole thermal energy storage is compared to the cost that the low-temperature solar collector contributes. The research has been done on an existing building in Umeå, Sweden. First, a model of a low-temperature solar collector was built in MATLAB. The model was then validated against the solar thermal collector model in TRNSYS developed by Bengt Perers, senior researcher at Technical University of Denmark. The energy output from the low-temperature solar collector together with the energy demands and the electricity consumption of the heat pump for the investigated building were used as inputs to the model of the borehole thermal energy storage in Earth Energy Designer. Despite the relatively large cooling demand for the examined building that could be used for charging, the results shows that it would be possible to have a smaller borehole thermal energy storage, if it was recharged with a low-temperature solar collector. If such an energy system would be built today it would be possible to lower the total investment cost of the energy system, if recharging the borehole thermal energy storage with a low-temperature solar collector.
Keywords: Samhällsbyggnadsteknik; Hållbar utveckling; Annan samhällsbyggnadsteknik; Energi; Innovation och entreprenörskap (nyttiggörande); Civil Engineering; Sustainable Development; Other Civil Engineering; Energy; Innovation & Entrepreneurship